Evaluación numérica de viviendas ecoamigables conformadas por botellas de plástico rellenas de arena y reforzadas con acero corrugado - Solarte Benavides, Alexander; Silva Ribón, Hugo Alfredo; Nova Burgos, Elías Daniel David (Ingeniería Solidaria, 2023)
This paper presents an experimental evaluation of eco-friendly houses made of plastic bottles (PET) filled with sand and reinforced with corrugated steel. The study was carried out in the structure’s laboratory located in Santo Tomas University, Villavicencio - Colombia.Introduction: PET is a poorly biodegradable material that has become an environmental pollution problem. Alternative construction systems with PET bottle recycling can supply construction functions taking advantage of their mechanical characteristics, as well as reduce environmental pollution through recycling and lowering construction costs.Methods: The bottles and reinforcing steel were placed vertically to provide lateral stability to the proposed system. A characterization of the mechanical properties of the proposed elements was carried out and a numerical model was built in finite elements with the aim of representing an approximation of the real behavior of a house that meets the requirements of the NSR-10.Results: It was determined that the structure will support the loads by calculating an ISE of 0.8 for sustainable walls and that it does not present excessive deformations according to an IFL of 0.9.Conclusions: The house supported the vertical loads, demonstrating that the system provides security to its occupants and that the construction system generates a reduction in costs.Originality: Although we can find houses built with bottles filled with sand, they are generally built with the bottles placed horizontally. This project proposes the study of houses made up of bottles located vertically in order to take advantage of their geometric properties and increase compressive strength.
Keywords: filled PET bottles; alternative construction systems; eco-friendly houses